PERBANDINGAN TINGKAT KEBUGARAN JASMANI ANTARA MAHASISWA PENDIDIKAN OLAHRAGAÂ DENGAN MAHASISWA PENDIDIKAN KEPELATIHAN OLAHRAGA - ERIKO PRATAMA, NANDA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Healthy and fit body is certainly everyone’s dream. Yet not everyone really knows for sure whether their body is fit enough or not before running fitness test. Good physical fitness is the main key for a person to perform repetitive physical activities in a relatively long time. The purpose of having a good physical fitness is to be able to perform daily activities efficiently without causing excessive fatigue. To identify and assess a person's level of physical fitness can be done by doing some kind of test, such as using Multistage Fitness Test (MFT), which refers to the norms introduced by Brianmac. This study aims to compare the level of physical fitness between students of physical education and students of sport coaching education of the year 2011 at Faculty of Sport Science, State University of Surabaya. This research is a comparative study using a comparative study design. The population of this study is all students of sport education major and sport coaching education major of the year 2011  consisting of 255 students. The samples of this study are taken  by using cluster random sampling in which consist of  1 class of physical education major and 1 class of sport coaching education major of the year 2011. Data analysis used in this study is the description of the data and test requirements. Based on the results of the study, there are no differences in physical fitness between the students of physical education major and students of sport coaching education major of the year 2011. Because students of physical education of 2011 get greater grades of significance (P value) than the value of alpha (5%) or in other words Sig 0.05> α (0.200> 0.05), so it is decided that H0 is accepted, which means that the data meet the normal  assumption. Mean while, the students of sport coaching education of 2011  also get greater grades of significance (P value) than the value of alpha (5%) or in other words Sig 0.05> α (0.068> 0.05), so it is decided that H0 is  accepted, which means that the data meet the normal assumption. The average level of physical fitness of physical education students is 38.277 and sport coaching education students is 39.762 with the level difference of physical fitness by 1.449. Keywords: Physical Fitness, Multistage Fitness Test (MFT), Students